Ekonomi Kreatif Berbasis Wana Wisata Sumber Biru dalam Meningkatkan Pendapatan Di Desa Wonomerto Wonosalam Jombang.: Ekonomi Kreatif Berbasis Wana Wisata Sumber Biru dalam Meningkatkan Pendapatan Di Desa Wonomerto Wonosalam Jombang. - Muchtolifah, Muchtolifah; Fitria Utami, Anisa; Izul, Imron (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
The development of a creative economy based on culinary tourism is starting to be liked by the community and culinary tourism is a new opportunity in the economic field because it offers tourist destinations supported by the freshness and richness of the culinary arts in their respective regions. This concept combines natural resources with their beauty and human resources with their intellect as assets in the manufacturing industry economy into a creative industrial economy. Through several policies and laws, the Indonesian government pays special attention to the economic development sector in the culinary tourism sector. Since the development of this culinary tourism, many entrepreneurs have succeeded in developing creative economy businesses in the culinary tourism sector. This research explores the role of innovation as the key to developing culinary tourism destinations to support economic growth in the area. The qualitative method is the method that we consider appropriate to conduct research and exploration of this culinary tourism. As a business that pours natural wealth, culinary wealth, and fresh new ideas into the development of the creative economy, it depends on innovation. In this research process, we also found innovations that are the key to the success of the creative economy in maintaining and developing its business. This has a positive impact on regional economic growth.